Adaptation period caracteristics in high - altitude newborn - Valero Ramos, Wilson Ronny (2009)
Introduction: Birth is a mandatory environmental change for the fetus when turning into a newborn. The adjustment processes that occcur in the minutes following childbirth are crucially important for the babys survival in the extrauterine environment. High-altitude environmental conditions, particularly hypobaric hypoxia, make this adjustment period different from what occurs in babies born in a normoxic envirronment. Objectives: To describe the characteristics of the adjustment period for high-altitude newborns. Also, we measured both cardiac and respiratory rates during the adjustment period in high-altitude newborns. Materials and methods: This is a prospective, longitudinal and analytical study, where 81 female and male newborns selected according to inclusion and exclusion criteria were assessed. The study was performed in EsSALUD Hospital in Juliaca, a city located at 3828 meters above sea level. Results: Oxygen saturation progressively increased, from an average 69.1 percent at 5 minutes, 79.6 percent at 15 minutes, and 88 percent at 30 minutes, stabilizing at 120 minutes, where the value was 90.5 percent on average. Cardiac rate was on average 167.7 beats per minute at 5 minutes, and it progressively decreased, to 162.9 at 15 minutes, and it stabilized from three hours of age on. Respiratory ratewas 68.3 at 5 minutes, 65.8 at 15 minutes, 60 at 30 minutes, and it stabilized in 54.6 breaths per minute at 120 minutes. Conclusions: The adjustment period for high-altitude newborns is longer compared to that reported in low-altitude newborns. Both respiratory and cardiac rates stabilize around 6 hours of age. Oxygen saturation, which is low at birth becomes stabilized after 6 hours of life.